1975
DOI: 10.1104/pp.56.6.816
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Properties of Mitochondrial Membrane from Dry Pea Seeds and Changes in the Properties during Imbibition

Abstract: An attempt to isolate intact mitochondria from dry pea seeds (Pisum sativum var. Alaska) ended in failure. Cytochrome oxidase in crude mitochondrial fraction from dry seeds was separated into three fractions by sucrose density gradient centrifugation. Two of the fractions contained malate dehydrogenase, whereas the other did not. Equilibrium centrifugation of mitochondrial membrane on sucrose gradients revealed that the membrane from the fraction without malate dehydrogenase was lighter than that from the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
1

Year Published

1977
1977
1988
1988

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 9 publications
(7 reference statements)
0
17
1
Order By: Relevance
“…Studies with peas have shown that mitochondrial intactness is correlated positively with germination and imbibition time (31). The percentages of GDH activity recovered in the 23 C mitochondrial pellets for both axes and cotyledons were much higher (100 and 42%, respectively) than in the previous study at 2 days (10), indicating that the extraction medium employed in this study was more suitable for isolating mitochondria.…”
Section: Methodscontrasting
confidence: 43%
“…Studies with peas have shown that mitochondrial intactness is correlated positively with germination and imbibition time (31). The percentages of GDH activity recovered in the 23 C mitochondrial pellets for both axes and cotyledons were much higher (100 and 42%, respectively) than in the previous study at 2 days (10), indicating that the extraction medium employed in this study was more suitable for isolating mitochondria.…”
Section: Methodscontrasting
confidence: 43%
“…The amount of GDH activity recovered from particulate (mitochondrial) fractions was 66.7 ± 8.8% and 36.1 ± 5.1% of the total activity for axes and cotyledons, respectively, after 48 hr at 23 C. In general, preparations increased in the percentage of mitochondrial dehydrogenases (GDH, MDH, and NADP-ICDH) recovered in the mitochondrial pellet (20,000g) over the course of the experiment (data not shown). This was true for both treatments and may have been due to increased mitochondrial integrity as has been shown to occur with imbibition in legumes (33). All GDH should have been mitochondrial in origin (7,35) at this stage of development with any recovery of the enzyme in the supernatant due to mitochondrial disintegration.…”
mentioning
confidence: 60%
“…Studies with legumes have shown that during imbibition and germination rapid changes occur in mitochondrial respiration (24,33). Dehydrogenases are of particular importance in cold acclimation due to their production of reduced nucleotides necessary for energy transduction (1,19 All dehydrogenases were assayed spectrophotometrically utilizing a Gilford 2000 spectrophotometer equipped with a H20-jacketed cuvette chamber for temperature control.…”
mentioning
confidence: 99%
“…Moreover, pelleting ofthe early mitochondria required a higher centrifugal force than that of mature mitochondria. A comparably wide distribution of Cyt oxidase in sucrose gradients has also been demonstrated after isolation of early mitochondria from several seed species (15,18,20). Since in these studies no malate dehydrogenase could be liberated from the dispersed zones of Cyt oxidase activity, the latter were taken to represent the remnants of fragile mitochondria that had lost their matrix.…”
mentioning
confidence: 99%